(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article raises a problem of teaching high school students the Ukrainian language (through the example of phraseology) within the framework of competence-based education paradigm. It focuses on the formation of key competencies, among which “Communication in foreign languages” holds pride of place, includes the ability to appropriately understand an utterance made in foreign language, to make assumptions and interpret concepts, thoughts, feelings, facts, views in oral and written form (by means of listening, speaking, reading, and writing) in a wide range of social and cultural contexts. The paper analyzes legislative and regulatory groundwork, educational and methodological assistance within the linguo-didactic category under study. It provides instructional guidelines on formation of high school students’ key competence “Communication in foreign languages”, which will facilitate increase in practical focusing on teaching phraseology, formation of school students’ communicative competence based on digesting phraseological categories, use of set expressions in the course of foreign language activity. There were defined the phraseological units which are worth using while teaching the Ukrainian language in complex relationship with English. The methodology created involves work on awareness of the role of phraseological units in reflection of national-cultural peculiarities, which helps place school students’ greater focus on diversity of cultural and linguistic worldimage.